TENDENCY OF PUNISHMENT OF TRAFFICKING OFFENCES IN CHINA - Ping, Sun (REVISTA ESMAT, 2025)
The Chinese Criminal Law of 1997 has stipulated all trafficking offenses related to firearms, antiquities, wildlife, human beings and drugs, and included aggravated penalties allowing for the death penalty for all of these offenses. In the more than 20 years since then, ten Amendments have been instituted to reform and to readjust the Criminal Law in the spirit of safeguarding social harmony, assuring human rights, and carrying out a policy of severity tempered with gentleness, in accordance with emerging world trends. The Supreme Court of China has tried to guide and unify the implementation of Criminal Law and criminal policy under its jurisdiction by publishing judiciary explanations.